A 65-Year-Old Female from Connecticut with Orf Infection - Jose Ramón Estela Cubells; Irwin Braverman; Michael Kashgarian; Rossitza Lazova (MDPI AG, 2016)
The virus, which causes orf and induces acute pustular skin lesions in sheep and goats, is transmissible to humans yet is rarely observed in North America. We present a case of a 65-year-old female farmer from Connecticut who contracted orf from her sheep. The clinical and histopathologic features, important to arrive at the correct diagnosis of this uncommon yet important infection, are described. We also discuss the benign nature of this condition and emphasize that treatment is not required.